Spermidine modulates pollen tube growth by affecting the factors Involved in pollen tube elongation - ÇETİNBAŞ GENÇ, ASLIHAN (My University, 2023)
Putrescine, spermine, and spermidine are among the most significant polyamines for plant growth and development, including pollen tube elongation. Although the effects of putrescine and spermine are well-known on tube elongation, little is known about the impact of spermidine. The aim of this study is to reveal how exogenic spermidine impinges positively and negatively on the factors involved in tube elongation such as actin cytoskeleton organization, calcium, pH and reactive oxygen species gradients, sucrose synthase enzyme activity, distribution of cell wall polysaccharide, tube nuclei movement. Treatment of 0.01 mM spermidine which showed a positive effect, increased actin dynamism, and, caused a decrease in the amount of cellulose in the tube apex by coordinating the sucrose synthase enzyme localization. These changes were reflected in the tube elongation velocities and oscillations as an increase, allowing the tubes to elongate faster. Treatment of 0.5 mM spermidine which showed a negative effect, caused changes in intracellular calcium, pH and reactive oxygen species gradients and these alterations reduced the dynamism of actin filaments. Decreased actin dynamism affected the localization of the sucrose synthase enzyme, inhibited the transport of newly synthesized wall materials to the tube apex and the transport of the generative nucleus to the tube apex. These changes were reflected in the tube elongation velocities and oscillations as a decrease, allowing the tubes to elongate slower. Results could be contributed to the explanation of the effect of spermidine in plant growth and development, including pollen tube elongation.
Keywords: Tarımsal Bilimler; Ziraat; Bitki Koruma; Fitopatoloji; Toprak ve Bitki Besleme; Toprak Verimliliği ve Gübreleme; Agricultural Sciences; Agriculture; Plant Protection; Phytopathology; Soil and Plant Feed; Soil Fertility, Acidity, Alkanility; Tarım ve Çevre Bilimleri (AGE); Bitki ve Hayvan Bilimleri; Tarım Bilimleri; BİTKİ BİLİMLERİ; TARIM BİLİMİ; Agriculture & Environment Sciences (AGE); PLANT & ANIMAL SCIENCE; AGRICULTURAL SCIENCES; PLANT SCIENCES; AGRONOMY; Agronomi ve Mahsul Bilimi; Yaşam Bilimleri; Bitki Bilimi; Agronomy and Crop Science; Life Sciences; Plant Science; Exogenous treatment; Pollen tube elongation; Polyamines; Spermidine